Haemopoietic growth factors. - Ketley, N. J. (BMJ Group, 1997)
Haemopoietic growth factors are involved in the production of the various blood cells from progenitors in the bone marrow, making them useful in a range of clinical situations. The genes for several of them have been cloned and their production engineered by recombinant technology, making them widely available. Myeloid growth factors are used to support patients in the aftermath of chemotherapy and bone marrow transplantation and have potential application in the treatment of infectious diseases. Erythropoietin is widely used for patients with anaemia due to failure of marrow production, having established its effectiveness in chronic renal failure. Thrombopoietin has recently been described and may provide a means to alleviate thrombocytopenia. Current indications and areas of recent reappraisal are addressed in this review.